Stability Analysis of Al Safarkia Dam Using Abaqus - حماد, منذر; نوت, مدين (Latakia University Journal -Engineering Sciences Series, 2021)
This study explains a method of calculating the stability of concrete gravity dams. Using the Finite Element Method (FEM), the study calculates the safety factors, against sliding and overturning of the target dams and presenting its results. we verified the stability of Al Safarkia dam using this method before and after the impact of a supposed earthquake with peak ground acceleration of 0.4g. this study concludes that the most dangerous loading case is the case of the least safety factors, consequently, all stresses whose maximum value reached 21 t/m2 were within the permissible values. the results of this study are discussed, analyzed and interpreted. Therefore, some Important conclusions and recommendations are stated.